The uniqueness of old shophouses Thye Ann Hotel and Restaurant at Jalan Hilir Kota Bharu, Kelantan - Mohd Jain Noordin, Mohd Azri; Maharimi, Mohammed Fadzli; Mohd Razali, Noorul Huda; Aziz, Salmiah; Bahauddin, Azizi (2025)
This research delves into the distinctiveness of old shop houses by focusing on an example The Thye Ann Hotel and Restaurant shophouses situated on Jalan Hilir, in Kota Bharu state of Kelantan in Malaysia. Traditional shop houses, in Malaysia carry cultural importance as they embody a mix of architectural legacy influenced by colonial times and communal beliefs. The Thye Ann Hotel and Restaurant shophouses serve as an illustration of these characteristics by reflecting the rooted history and identity of Kota Bharu state. This research used a method that involves conducting, on site observations and interviewing the building owner and experts to investigate the significance as well, as the cultural and historical values associated with these buildings. The research findings show that the design style of the Thye Ann Hotel and Restaurant shophouses blends elements, with colonial influences by incorporating features like tall ceilings and detailed cornices that were adjusted from Western styles to suit the tropical weather conditions. The frontage of the building displays characteristics such as pilasters and intricate carvings combined with design elements like timber and clay tiles. This blend of styles reflects the building’s ability to adapt and its distinct identity, within Kota Bharu shophouses.